ANALYSIS OF ACCOUNTING SYSTEM IN SALES CV. DUTA JAVA TEA INDUSTRI (Tea 2Tang) TEGAL - One, Wahyuni; Isafaatun, SE., MM, Eliya; ekowati, SE., MM, Dhiana (Accounting, 2009)
The purpose of this study was to determine the accounting system cash sales that happened on the CV. Duta Java Tea Industri (2 Tang Tea). The problem in this research is